(3NRf GSJQLGY GdeYdheGJs - (3YUGe GMeO(B, (3GdfOGas; (3YGeQ YHO Gddg TbQ(B, (3Gjef GdTfWjs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2009)
(3CSGSjGJ GSJQLGY GdeYdheGJ , GdJMdjd GdehVhYj , GddZI aj GdGSJQLGY , GdHMK aj eQGUO GdHjGfGJ , GdYhGed GdeDKQI Ydi GdCOGA aj GSJQLGY GdeYdheGJ , GdWQb GdBdjI dGSJQLGY GdeYdheGJ (B.s
(3eQGLY U(B.254s
Keywords: (3GdeYdheGJs; (3JcfhdhLjG GdeYdheGJs; (3NOeGJ GdeYdheGJs; (3Yde GdeYdheGJs